Employment Impact of Fringe Benefits in Canadian Manufacturing Sector : 1957-1965 - Hameed, Syed (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1973)
The paper analyzes the growing costs of various fringe benefits in Canada and their impact on expanding employment. The empirical evidence is in support of fringe barrier hypothesis but not until labour turnover costs are added to fringe costs. It emphasizes that Canadian data on fringe benefits and overtime are extremely inadequate therefore, at the present time, no conclusive study is possible without collecting data on overtime, describing the causes of assigning it internally in a factory. This study attempted to fill in this gap by suggesting that external factors such as skill shortages and capacity output are not significant determinants of overtime.